Epidemiology of ankle sprains and anterior cruciate ligament injuries in youth basketball athletes in Niigata, Japan: A regional survey on injury management and healthcare professional involvement - Takanori Kikumoto; Jun Mizutani; Atsushi Tsuchida; Tomoya Takabayashi; Masayoshi Kubo; Hirokazu Okada; Yoshiaki Kon (PLoS ONE, 2026)
Objective Ankle sprains are highly prevalent among youth basketball players, particularly in the under-15 age group, and inadequate post-injury management may contribute to the development of chronic ankle instability and may be associated with an increased risk of anterior cruciate ligament injuries. This study aimed to determine the incidence of ankle sprains and post-injury management among under-12 and under-15 basketball players through a large-scale questionnaire survey. Additionally, we examined the prevalence of chronic ankle instability and anterior cruciate ligament injuries to assess the epidemiological impact of ankle sprains on young athletes. By examining these age groups, this study aimed to provide insights into potential preventive strategies and the need for appropriate medical intervention during early athletic development. Methods A cross-sectional survey was conducted to assess ankle sprain history, medical consultation rates, prevalence of chronic ankle instability, and anterior cruciate ligament injuries. The study targeted school and club basketball teams in Niigata, Japan. Overall, 2,747 youth basketball players from under-12 and under-15 age groups participated. Results Ankle sprains were more common in under-15 players (61.2%) than in under-12 players (39.0%). Medical consultation rates were lower in under-15 players (56.6%) than in under-12 players (80.1%). Chronic ankle instability was found in 12.4% of the players. Among under-15 players, 0.9% underwent anterior cruciate ligament reconstruction, and half of them had chronic ankle instability. Many players returned to play despite experiencing pain. Conclusions The coexistence of chronic ankle instability and anterior cruciate ligament injuries suggests a possible association between these conditions; however, causal relationships cannot be inferred because of the cross-sectional study design and the small number of anterior cruciate ligament cases.